PENGGUNAAN METODE FUZZY PADA PENGISIAN TANDON AIR OTOMATIS DENGAN MICROCONTROLLER - Suherman, Suherman; Risnawati, Risnawati; Ananda, Ricki (STMIK Royal Kisaran, 2023)
Abstract : A mosque is a building used by Muslims to get closer to the creator by worshiping and observing Islamic law. Efficient water management in mosques is essential to support the sustainability and efficiency of natural resources. This study proposes an automatic water reservoir filling system in mosques using microcontroller technology. The fuzzy method is useful in filling automatic water reservoirs with microcontroller technology as an optimization and regulating the water filling process automatically. This system is to automate the process of filling water reservoirs by utilizing intelligent water level sensors and microcontrollers. In this research, I created a system that is able to detect the water level in the reservoir and regulate the filling process automatically. The use of a water level sensor allows accurate measurement of the water level, while the microcontroller controls the water pump according to the detected needs. The test results show that the implementation of microcontroller technology in filling automatic water reservoirs in mosques can increase water use efficiency and reduce waste. The system provides an effective and environmentally friendly solution for managing the mosque's water needs, contributing significantly to water conservation and maintenance of natural resources. Keywords : water reservoir; mosque; microcontroller; fuzzy method; water level sensor Abstrak : Masjid adalah sebuah bangunan yang digunakan umat muslim untuk mendekatkan diri kepada sang pencipta dengan beribadah dan menjalankan syariat agama Islam. Pengelohan air yang efisien di masjid sangat penting untuk mendukung keberlanjutan dan efisiensi sumber daya alam. Penelitian ini mengusulkan sebuah sistem pengisian tandon air otomatis di masjid menggunakan teknologi microcontroller. Metode fuzzy berguna dalam pengisian tandon air otomatis dengan teknologi microcontroller sebagai pengoptimalkan dan mengatur proses pengisian air dengan secara otomatis. Sistem ini untuk mengotomatiskan proses pengisian tandon air dengan memanfaatkan sensor water level dan microcontroller yang cerdas. Dalam penelitian ini, dibuat sistem yang mampu mendeteksi tingkat air dalam tandon dan mengatur proses pengisian secara otomatis. Penggunaan sensor water level memungkinkan pengukuran yang akurat terhadap tingkat air, sementara microcontroller mengontrol pompa air sesuai dengan kebutuhan yang terdeteksi. Hasil pengujian menunjukkan bahwa implementasi teknologi microcontroller dalam pengisian tandon air otomatis di masjid dapat meningkatkan efisiensi penggunaan air dan mengurangi pemborosan. Sistem ini memberikan solusi yang efektif dan ramah lingkungan untuk mengelola kebutuhan air masjid, memberikan kontribusi signifikan terhadap konservasi air dan pemeliharaan sumber daya alam. Kata kunci: tandon air; masjid; microcontroller; metode fuzzy; sensor water level